Prevalence of overweight among Malaysian adults from rural communities - Khor, Geok Lin (Asia Pacific Journal of Clinical Nutrition, 1999)
Assessment of the nutritional status of 4054 households from rural communities in Peninsular Malaysia was undertaken from 1992 to 1995. Body mass index (BMI) and waist-to-hip ratio (WHR) were obtained from a self-selected sample of 1854 men and 2741 women aged ≥ 18 years. The BMI and WHR results are presented according to gender, age groups and type of community as defined by the main occupation, namely, fishing, rice farming, estate work, rubber and coconut small-holding. The mean BMI for men and women of all age groups are 22.5 kg/m2 and 23.8 kg/m2, respectively. The mean BMI for both genders increases with age between 18.0 and 49.9 years, after which the value declines. The prevalence of pre-obese (BMI ≥ 25.0-29.9 kg/m2) is 19.8% for men and 28.0% for women. The prevalence of obese men and women (≥ 30.0 kg/m2) is 4.2% and 11.1%, respectively. The highest prevalence of pre-obese and obese men is found in the age groups of 30.0-49.9 years, while that for women is in the 40.0-49.9 years age group. The prevalence of pre-obesity and obesity is higher in women than in men for every age group. A similar result was indicated by WHR whereby a higher proportion of women (22.5%) than men (5%) for all ages was found to show central obesity. The prevalence of overweight adults is higher when compared with previous studies on subjects from almost similar rural communities. This study indicated that overweight is on the increase in rural communities, especially among female subjects.